AN ASSESSMENT OF FAITH-BASED ORGANISATIONS AND PEACEBUILDING IN KADUNA STATE, NIGERIA, 1999-2012 (2016)
Peacebuilding is central to establishing sustainable peace after violent conflict has de-escalated. Existing studies on peacebuilding in Kaduna state are replete with the roles of faith-based organisations. However, these studies have not optimally explored the effectiveness of activities by faith-based organisations on peacebuilding in Kaduna state. This study, therefore, examined the activities of faith-based organisations with a view to evaluating their strengths and weaknesses towards advancing peacebuilding in Kaduna State, Nigeria, from 1999 to 2012. The study was premised on social capital theory and adopted descriptive survey design. Three faith-based organisations (Interfaith Mediation Centre, Federation of Muslim Women Association and Development and Peace Initiatives of Catholic Church) in Kaduna were purposively selected because of their involvement in peacebuilding. Six hundred and fifty two respondents were randomly selected from seven local government areas (Markafi, Chikun, Kachia, Kaduna North, Kaduna South, Lere and Zango Kataf) in the three senatorial districts (Kaduna North, Kaduna South and Kaduna Central) where peacebuilding had been carried out. A structured questionnaire was used to elicit information on activities of faith-based organisations on peacebuilding and challenges experienced. This was complemented with five sessions of focus group discussions with members of staff of the faith-based organisations and 18 in-depth interviews with religious leaders and non-participant observations. Quantitative data were analysed using descriptive statistics, while qualitative data were content analysed. About 73.8% of respondents were aged 26-45 years, 47.7% were married and 58.8% were Christians. Respondents identified dialogue (62.8%), education (63.0%), advocacy (63.0%), and mediation (62.8%) as highly supportive activities of faith-based organisations on peacebuilding in Kaduna state, Nigeria. Workshops, peace accord signing among groups, counseling, enlightening campaign, community participatory programmes on governance and capacity building were some of the programmes that constituted activities of faith-based organisations on peacebuilding in Kaduna State. Each of the selected faith-based organisations had expansive social network, which included contacts that cut across religion, gender, age and ethnicity for the purpose of establishing sustainable peace between groups, institutions and the state. Rise in fanatical and intolerant groups (62.6%) and insufficient funds (63.4%) constituted challenges to faith-based organisations in advancing peacebuilding in Kaduna state. Long term presence, strong faith motivation for peacebuilding and spiritual authority were some of the strengths of the faith-based organisations. Accusations and risks of proselytising constituted the major weaknesses of faith-based organisations. Activities of faith-based organisations were fundamental to rebuilding of good communities’ relationship and development of constructive relations among conflicting groups in Kaduna State, Nigeria. Dialogue, education, advocacy, and mediation should be sustained for peacebuilding